2018
DOI: 10.1292/jvms.17-0001
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory effect of Genistein on granulosa cell in ovary of rat with PCOS through Bcl-2 and Bax signaling pathways

Abstract: The effect of genistein on Bcl-2 and Bax protein expression in the ovarian tissue of rats with polycystic ovarian syndrome (PCOS) was evaluated. Sixty rats were divided into six groups. Rats in the Dose group received genistein at a concentration of either 5 (L-gen), 10 (M-Gen) or 20 (H-Gen) mg per kg of body weight per day. The expression of Bcl-2 mRNA and Bax mRNA was determined by in situ hybridization. Bcl-2 and Bax protein concentration was quantified by ELISA. The results showed that the expression of Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Therefore, these findings confirmed that GEN overwhelmed E2 in improving the apoptotic events occurring in the ovary due to γ-radiation. These results reinforce the previous report stating that GEN improved ovarian function in the polycystic ovary model by reducing cell apoptosis 47 . Together, these results indicate that the radioprotective effect of GEN over E2 in attenuating ovarian injury could be through its antioxidant properties and modulation of the mitochondrial apoptotic pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, these findings confirmed that GEN overwhelmed E2 in improving the apoptotic events occurring in the ovary due to γ-radiation. These results reinforce the previous report stating that GEN improved ovarian function in the polycystic ovary model by reducing cell apoptosis 47 . Together, these results indicate that the radioprotective effect of GEN over E2 in attenuating ovarian injury could be through its antioxidant properties and modulation of the mitochondrial apoptotic pathways.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, whether GEN in different doses is related to IGF-1 and IGFBP-1 changes in animal experiment and clinical study or not has not been evaluated previously. In our previous study (Chi & Zhang, 2013;Chi et al, 2018), we had confirmed that GEN could regulate the levels of hormones in the ovary of young female rats and related proteins and genes such as Bcl-2, Bax and P450 mRNA in ovarian granulosa cells. On this basis, in order to further research the regulation effect of GEN on ovarian function, we select IGF-1 and IGFBP-1, the key factors influencing the process of follicular development, as the research targets and determine their expression levels in serum and ovary.…”
mentioning
confidence: 64%
“…Although a number of experiments have been performed to correlate isoflavones and PCOS in rats, only a handful have investigated the relationship between the intake of isoflavones and PCOS in humans. These studies described improvements in plasma lipid and androgen profiles after three to six months of isoflavone interventions in PCOS women [ 26 , 87 , 88 , 89 , 90 , 91 , 92 ]. Most of these studies have already given promising results based on markers of insulin resistance, hormonal status, triglycerides, and biomarkers of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%